Mineral nutrition of rice and post-harvest soils influenced by self-made organic composts - Akter, Suma; Khan, Md Harunor Rashid; Saha, Mithun Kumar (Bangladesh Journal of Scientific and Industrial Research, 2023)
Using self-made organic composts i.e., rice hull compost (RHC), rice straw compost (RSC), sawdust compost (SDC), and Vermicompost (V) an experiment was conducted to evaluate their responses on mineral nutrition of rice and post-harvest soils under field condition. The total nitrogen contents among the treatments ranged from 9.6 - 21.4, phosphorus: 1.1 – 4.42, potassium: 3.86 - 7.27, sulfur: 11.9 – 19.7, calcium: 3.30 – 11.87 and magnesium: 2.76 – 5.54 g kg-1 at the maturity stage of rice plants which were found to be positively influenced by the applied organic composts. The nutrient status of the post-harvest soils was also influenced by the applied organic composts. The maximum amount of 78.29 mg kg-1 available N was recorded in the T3 treatment, where available nitrogen content increased by 85.65% as compared to the control plot. There were significant (p ≤ 0.05) increases in other nutrient contents with the increased doses of the composts under rice production. Bangladesh J. Sci. Ind. Res. 58(2), 99-106, 2023